First record of the invasive Asian clam Corbicula fluminea (O.F. Müller, 1774) (Bivalvia: Corbiculidae) in Slovenia - Teja Bizjak Govedič; Marijan Govedič (Natura Sloveniae)
The Asian clam (Corbicula fluminea) is considered one of the most invasive freshwater bivalves in the world. It has been introduced to several European countries. During the field surveys conducted in August 2018, a total of 61 specimens of the Asian clam were found along the Drava River between Ormož and Središče ob Dravi in Northeast Slovenia. These are the first records of this invasive species’ occurrence in Slovenia.